Cost-effectiveness of obinutuzumab plus bendamustine followed by obinutuzumab monotherapy for the treatment of follicular lymphoma patients who relapse after or are refractory to a rituximab-containing regimen in the US. (3rd October 2018) - Guzauskas, Gregory F.; Masaquel, Anthony; Reyes, Carolina; Bernaards, Coen; Krivasi, Tania; Veenstra, David L.
Abstract: Aims: Obinutuzumab (GA101, G) was approved in February 2016 by the US Food and Drug Administration to treat follicular lymphoma (FL) patients who relapsed after, or are refractory to (R/R), a rituximab-containing regimen (R/R-rituximab). In the GADOLIN trial, R/R-rituximab patients who received G plus bendamustine (B) followed by G-monotherapy (G + B) for up to 2 years had significantly improved progression-free survival and overall survival compared to patients receiving B-monotherapy. This study estimated the cost-effectiveness of G + B vs B-monotherapy for R/R-rituximab FL patients from a US payer perspective. Materials and methods: Patient outcomes were simulated using a 3-state area under the curve model including progression-free survival, progressive disease, and death. This study used R/R-rituximab data from the National LymphoCare Study to extrapolate the GADOLIN trial's refractory FL progression-free and overall survival data to a R/R-rituximab FL population. Drug utilization and adverse events were based on trial data, and costs were based on Medicare reimbursements and drug wholesale acquisition costs in 2016. Utility estimates were derived from published literature. Post-progression treatment costs were based on observed post-progression therapies in GADOLIN. Sensitivity analyses were conducted to assess model uncertainty. Results: G + B resulted in an increase in quality-adjusted life years relative to B-monotherapy of 1.24 (95% CR = 0.61–1.87); the incremental total cost was $58, 100 (95% CR = $54, 500–$61, 500). The incremental cost-effectiveness ratio was $47, 000 per QALY gained, and, based on probabilistic simulations, there was a 98% probability that G + B was cost-effective at the $100, 000 per QALY threshold. Limitations and conclusions: This US-based analysis suggests that treatment with G + B compared to B-monotherapy is likely cost-effective in R/R-rituximab FL patients. Modeling a R/R-rituximab population based on a synthesis of GADOLIN and the National LymphoCare Study data introduces uncertainty in the analysis. However, the findings were robust to sensitivity analyses.